VALUE CONSTRUCTION OF MANYANDA TRADITIONAL AT NAGARI TALANG, SOLOK DISTRICT - Muhammad Rizki; Febri Yulika (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research aims to examine the construction of values in the Manyanda tradition. The type of research used in this research is a qualitative research method with a case study approach. The data collection techniques used in this research are through observation, interviews and documentation. The research results obtained from the field are as follows: The Manyanda tradition is a valuable tradition in the lives of the people of Nagari Talang, Solok District as one part of the traditional death procession. It has existed for a long time as part of the social structure of society, and still survives today. However, based on findings in the field, there are a number of differences in perception between various groups in understanding the value construction of the Manyanda tradition. The Nagari elite such as traditional elders, niniak mamak, cadiak pandai and bundo kanduang have different understandings from society in general, especially among the younger generation. There is a shift in the value of the manyanda tradition from a social obligation as a form of replacing the position of a person who dies socially to just being a traditional obligation. This difference in understanding and perception has an impact on a shift in the meaning of the manyanda tradition for the community at Nagari Talang